Exposure to pesticide and its association with respiratory health among paddy farmers at Tanjung Karang, Selangor - Jalaludin, Juliana; Mohd Samsuddin, Nuranis Syfainie; Tualeka, Abdul Rohim (International Peer Reviewed Journals and Books, 2019)
Pesticide has been used by paddy farmers in their agricultural activities to increase rice crop yield since past few decades. However, the usage of this chemical with limited knowledge of its deleterious effects on health, community and environment without proper consideration of safety may cause chronic health problems such as respiratory health problems and lung dysfunction. This paper was conducted to determine the association of exposure to pesticide with respiratory health among paddy farmers at TanjungKarang, Selangor as exposed group and office workers working in TanjungKarang town as the comparative group. The results showed that the duration of exposure to pesticide between both groups were mostly low (86%) and high duration for only 4% for paddy farmers and none of office workers. There were significant differences in cough and phlegm, as they were higher among paddy farmers compared to the comparative group at ρ<0.001. Paddy farmers who were exposed to high levels of pesticide were 2 times more likely to have cough and 3 times more likely to get phlegm. FVC% (t=-1.470, p=0.001) and FEV1% (t=-1.526, p=0.001) were lower among the exposed group compared to the comparative group. The prevalence of abnormal FVC were found at 80% in exposed group and 38% in comparative group andabnormal FEV1 were found at 89% and 31% of respondents in both study groups. There was a significant correlation between long abnormalities for FVC% and exposure duration (χ2= 2.903, p= 0.001). This study concluded that the paddy farmers were at risk of respiratory symptoms, as reflected by the increase in the reported respiratory symptoms and lung function reduction.